The influence of hedonic values on s-commerce adoption behavior - Hashim, Kamarul Faizal; Mohd Yusof, Shafiz Affendi; Ahmad, Rahayu (American Scientific Publishers, 2015)
Social commerce is gaining its popularity and becoming one of the important platforms for online commerce.Despite the growing advantages associated with s-commerce adoption, very few studies were conducted to examine the motives that drive consumers to adopt s-commerce platform.Thus, this study contributes by examining the influence of hedonic values on consumer’s decision to adopt s-commerce.A theoretical model is proposed and validated using a quantitative methodology.The research finding shows that s-commerce adoption intention is influenced by strongly influenced by their intention.Meanwhile consumer’s intention to adopt s-commerce is influenced by adventure, idea, gratification, sociality and value.This paper concludes by suggesting practical suggestions on how to increase user’s hedonic value when using s-commerce platform.